Furthering sub-central autonomy in Europe? The roles of identity and redistribution - Joan Costa-i-Font (Intereconomics, 2014)
The European Union is regarded as a union of diverse territories, but this definition applies to most European Union member states, too. How best should member states manage diversity to maintain the Union? What are the main triggers for autonomy demands in a Union? This article contends that the progressive expansion of regional identities as a response to European integration acts as the main trigger of demand for regional autonomy. This paper draws upon descriptive evidence from two affluent and distinctive Spanish regions, Catalonia and the Basque Country, from 1982 to 2007. Explorative regression analysis of survey data suggests that sub-central identity exceeds that of taming regional redistribution in determining support for regional autonomy.
Keywords: 330; Europäische Integration; Selbstverwaltung; Baskenland; Katalonien